Healthcare System Adaptation Strategies in Response to Pandemics: Case Studies from Global Perspectives - Priya, S.; Iyer, Vaidyanathan R; Kalluri, Ram Chandra; Singh , Shashank Kishor; Raheja, Rohit; Gujarathi, Rahul Haridas; Das, Shiv Shankar (Journal of Ecohumanism, 2024)
The COVID-19 pandemic was unprecedented in the global health care systems, and this led to various responses from health systems in various countries. This article focuses on the case of China, Italy, the United States, and India to analyze their reactions and find out the best strategies of the healthcare system. The measures taken by China include quick lockdowns and the development of healthcare infrastructure, while the measures taken by Italy include the reliance on NGO support and regional interventions, the United States’ economic relief measures and vaccine development, and India’s strategic planning and resource mobilization. The comparative analysis shows that the main priorities in the fight against pandemics are the timely intervention, the availability of healthcare, communication, and cooperation with other countries. The implications of these findings suggest that policymakers should pay special attention to the healthcare system’s capacity and readiness. These include increasing the number of ICU beds, increasing the stock of PPEs, and having effective public health communication plans. The future research should be directed toward the consequences of pandemics, the efficacy of different interventions, and the use of technology in the healthcare system.